Experience of discrimination in egalitarian societies : the Sámi and majority populations in Sweden and Norway - Yasar, Rusen; Bergmann, Fabian; Lloyd-Smith, Anika; Schmid, Sven-Patrick; Holzinger, Katharina; Kupisch, Tanja (Ethnic and Racial Studies, 2024)
The Sámi people stand out as the only Indigenous minority in an egalitarian European context, namely the Nordic Countries. Therefore, inequalities that they may face are worth closer inspection. Drawing on the distinction between inequalities among individuals (vertical) and between groups (horizontal), we investigate how different types of inequalities affect the Sámi today. We formulate a series of hypotheses on how social, economic, cultural, and political inequalities are linked with discrimination experience, and test these with original data from a population survey conducted in northern Norway and northern Sweden simultaneously in 2021. The findings show that Sámi ethnic background increases the probability of experiencing discrimination. While individual-level economic inequality is also pertinent, this does not directly materialise as between-group inequality. Instead, minority language use is a strong predictor of discrimination experience, revealing the socio-cultural nature of ethnic inequalities. Cross-country differences are only reflected in the effect of minority language use. published